Transformasi Paradigma Administrasi Publik dalam Peningkatan Kualitas Layanan Pengukuran di Kantor Pertanahan Kota Gorontalo - Musdram, Maidon Christofel; Isa, Rusli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the transformation of the public administration paradigm in improving the quality of land measurement services at the Land Office of Gorontalo City. The transition from traditional bureaucracy to a more responsive, participatory, and innovative public administration system is an essential part of the reform of public services in Indonesia. Using a qualitative descriptive method through interviews, observations, and documentation, the study reveals that the implementation of new paradigms such as New Public Management (NPM) and New Public Service (NPS) has significantly improved service efficiency, accountability, and community satisfaction. However, several challenges remain, including bureaucratic rigidity, limited human resource competence, and uneven digital adoption. The findings suggest that sustainable transformation requires cultural change, capacity building, and technology-based service innovation to achieve high-quality, citizen-oriented land measurement services.